Advanced Cases of Birdshot HLA-A29 Retinochoroiditis: Prevalence and Characteristics - Elahi, Sina; Lages, Vania; Jeannin, Bruno; Herbort, Carl Peter (Klinische Monatsblätter für Augenheilkunde, 2020)
Purpose To establish the prevalence, morphological, and functional characteristics and evolution of advanced cases of birdshot retinochoroiditis (BRC).Methods A retrospective review of all BRC cases seen at the Centre for Ophthalmic Specialized Care, Lausanne, Switzerland, with at least 3 years of follow-up since the onset of symptoms. The following parameters were evaluated: demographic characteristics, best-corrected visual acuity (BCVA), fundus photographs, fluorescein (FA) and indocyanine green (ICGA) angiography frames, and visual field evaluation from initial visit to last follow-up.Results Out of the 1920 patients with uveitis who were followed from 1995 until 2018, 32 (1.67%) were diagnosed with BRC; 20 of these 32 patients had sufficient data to be included. Three of these twenty patients (15.0%) had severe forms of the disease. Two patients had received insufficient treatment and one progressed despite attempted maximal therapy. The mean BCVA was 0.62 (± 0.42) at presentation, which was already at an advanced stage of the disease, and 0.51 (± 0.37) at last follow-up. The average visual field mean defect (VFMD) was 19.65 (± 4.71 dB) at presentation and 21.40 (± 2.45 dB) at last follow-up. Choroidal inflammatory activity monitored by ICGA decreased from 10.67 (± 9.18) at presentation to 6.67 (± 5.61) at last follow-up. FA revealed mild retinal vasculitis at 6.50 (± 4.76), which remained stable to 4.67 (± 3.20). EDI-OCT estimated choroidal thickness (EDI-OCT-CT) measurements were 246.36 (± 116.93 µm) at presentation and 231.30 (± 120.70 µm) at the last follow-up.Conclusions In our setting, 15% of BRC cases had a severe course and suffered extensive irreversible chorioretinal damage, obviously due to insufficient treatment in two cases. This underlines the importance of correctly diagnosing BRC and initiating therapy as promptly as possible to avoid such outcomes in an otherwise possibly controllable disease.
Keywords: stromal choroiditis; birdshot; birdshot HLA-A29 retinochoroiditis; immunosuppressive therapy; severe disease